Obstacles and enablers of internationalization of Philippine SMEs through participation in global value chains - Jamil Paolo S. Francisco; Tristan Canare; Jean Rebecca Labios (Philippine Institute for Development Studies (PIDS), 2018)
Small, and medium-sized enterprises (SMEs) are important in many developing countries, including the Philippines. However, this sector remains much less productive than their large counterparts. One factor that can help SMEs achieve higher productivity is internationalization by connecting them to global value chains (GVCs). However, participating in GVCs is not easy for SMEs as they face a host of obstacles in doing so. This paper attempts to determine the challenges and enablers of connecting small and medium businesses to global value chains. It uses data from a survey of SMEs in Metro Manila and a set of key informant interviews of SME owners and of officials of government agencies tasked to assist SMEs. Findings show that Philippine SMEs are weakly linked to GVCs. The challenges and enablers can be grouped into five themes: 1) competition in ASEAN and East Asia; 2) international standards, regulatory requirements, and local institutions; 3) role of the government; 4) international market demand and inputs supply; and 5) entrepreneurial mindset. Based on the results, some policy implications were formulated.
Keywords: 330; small and medium enterprises; global value chains; internationalization; exports